2023
DOI: 10.1039/d2ta09236k
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the electronic structure of In2O3/C photocatalysts for enhanced CO2reduction

Abstract: Photoreduction of CO2 into value-added fuels under mild conditions is a promising route to relieve the pressure from extensive CO2 emission and energy consumption, but the rational design of novel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Figure c shows three peaks at 532.9, 531.4, and 529.5 eV in the O 1s spectrum. The peak at 532.9 eV corresponds to the chemisorbed oxygen species (O C ), the peak at 531.4 eV is attributed to the oxygen vacancy (O V ), and the peak at 529.5 eV is related to the lattice oxygen (O L ). , Figure S9 compares the variation of the oxygen vacancy content in the high-resolution O 1s spectra of different samples. Only lattice oxygen (O L ) and chemisorbed oxygen (O C ) species exist in pure In 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure c shows three peaks at 532.9, 531.4, and 529.5 eV in the O 1s spectrum. The peak at 532.9 eV corresponds to the chemisorbed oxygen species (O C ), the peak at 531.4 eV is attributed to the oxygen vacancy (O V ), and the peak at 529.5 eV is related to the lattice oxygen (O L ). , Figure S9 compares the variation of the oxygen vacancy content in the high-resolution O 1s spectra of different samples. Only lattice oxygen (O L ) and chemisorbed oxygen (O C ) species exist in pure In 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 532.9 eV corresponds to the chemisorbed oxygen species (O C ), the peak at 531.4 eV is attributed to the oxygen vacancy (O V ), and the peak at 529.5 eV is related to the lattice oxygen (O L ). 36,37 Figure S9 27 When loaded with Au nanoparticles, the increase of the chemisorbed oxygen (O C ) and defective oxygen is due to the catalytic effect of Au that enriches the surface or the interface of In 2 O 3 with reactive substances such as oxygen ions. 38 As shown in Figure 3d, the Co 2p orbital can be divided into four peaks, and the two peaks at 780.6 and 796.3 eV correspond to the 2p 3/2 and 2p 1/2 orbitals of Co 3+ , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their long lifetime and large Stokes shift, long afterglow materials have been widely studied, [1][2][3][4][5][6][7] which currently rely on light sources in the ultraviolet region for excitation as reported. It is also well known that UV light is detrimental to human beings 8 and is not frequently used in people's daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, various methods have been developed, such as constructing heterojunction, metal deposition, heteroatom doping, and so on. For example, the Shi group reported that a Cu-doped CeO 2– x with rich oxygen vacancies can improve light capture and charge transfer efficiency and can obtain a higher CO production rate of 1.65 μmol h –1 g –1 compared with the undoped one . Recently, the Lou group prepared the In 2 S 3 –CdIn 2 S 4 heterojunction catalyst and obtained an excellent CO 2 reduction rate (825 μmol h –1 g –1 ) under visible light.…”
Section: Introductionmentioning
confidence: 99%